2017
DOI: 10.1074/jbc.m117.778761
|View full text |Cite
|
Sign up to set email alerts
|

Protein arginine methyltransferase 1 modulates innate immune responses through regulation of peroxisome proliferator-activated receptor γ-dependent macrophage differentiation

Abstract: Arginine methylation is a common posttranslational modification that has been shown to regulate both gene expression and extranuclear signaling events. We recently reported defects in protein arginine methyltransferase 1 (PRMT1) activity and arginine methylation in the livers of cirrhosis patients with a history of recurrent infections. To examine the role of PRMT1 in innate immune responses , we created a cell type-specific knock-out mouse model. We showed that myeloid-specific PRMT1 knock-out mice demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 41 publications
5
61
0
Order By: Relevance
“…Recently we and others have found that PRMT1 is an immune regulator. Its targets include, but are not limited to, TRAF6, NFκB, PPARγ, c-Myc, STAT3, FOXOs and β-catenin all of which are involved in immune cell regulation, specifically immune cell polarization (7,9,10,21). Thus, it is not surprising that PRMT1 is involved in regulation of the tumor immune environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we and others have found that PRMT1 is an immune regulator. Its targets include, but are not limited to, TRAF6, NFκB, PPARγ, c-Myc, STAT3, FOXOs and β-catenin all of which are involved in immune cell regulation, specifically immune cell polarization (7,9,10,21). Thus, it is not surprising that PRMT1 is involved in regulation of the tumor immune environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that PRMT1 is an important regulator of immune signaling in multiple cell types including monocytes, liver macrophages, hepatocytes, liver tumor associated macrophages and hepatoma cells (8)(9)(10)18). In human HCC, PRMT1 overexpression is associated with poor prognosis ( Figure S3), suggesting that PRMT1 might promote tumor growth.…”
Section: Prmt1 Regulates Immune Checkpoint Gene Expression In Mice Anmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6NTac‐Prmt1 tm1a(EUCOMM)Wtsi /WtsiCnbc mice were obtained from EUCOMM (EUCOMM project: 40181) and bred with Flp recombinase mice to get homozygous Prmt1 floxed breeders as decribed . These mice were next crossed with Albumin‐Cre mice to generate mice lacking Prmt1 in hepatocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) was performed as described . Mouse liver tissue was homogenized, then cross‐linked by the addition of 1% formaldehyde for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%